2019
DOI: 10.3390/jcm8060845
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of miRNA in Helicobacter pylori-Induced Gastric MALT Lymphoma: From Mice to Human

Abstract: Gastric MALT lymphoma (GML) is directly caused by Helicobacter pylori infection but occurs only in a small number of infected subjects. Mechanisms underlying the initiation and progression of GML remain unclear. MicroRNAs (miRNAs) are small non-coding RNAs that are now considered as major players in inflammation and carcinogenesis, acting as oncogenes or tumor suppressors. Previous laboratory studies have shown in a GML mouse model that overexpression of a distinct set of five miRNAs (miR-21a, miR-135b, miR-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…Recently, Blosse et al showed that four novel miRNAs (miR-150, miR-155, miR-196a, and miR-138) played important regulatory roles in the pathogenesis of gastric MALT lymphoma caused by Helicobacter pylori infection [50]. Consistent with the results reported for gastric MALT lymphoma, we found that miR-138 was expressed at higher levels in biopsy tissues of orbital MALT lymphoma patients compared with IgG4-ROD.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, Blosse et al showed that four novel miRNAs (miR-150, miR-155, miR-196a, and miR-138) played important regulatory roles in the pathogenesis of gastric MALT lymphoma caused by Helicobacter pylori infection [50]. Consistent with the results reported for gastric MALT lymphoma, we found that miR-138 was expressed at higher levels in biopsy tissues of orbital MALT lymphoma patients compared with IgG4-ROD.…”
Section: Discussionsupporting
confidence: 90%
“…NF-kB and MYB directly activate the expression of miR-155 in B cells, provoking the unblocking of AKT activity and influencing BCR signaling. NF-kB and BCR activation plays a key role in MALT lymphomagenesis [ 23 ]. Former studies have shown the upregulation of miR-142 and miR-155 when comparing human GML tissue to normal mucosa [ 24 ] and chronic gastritis [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Former studies have shown the upregulation of miR-142 and miR-155 when comparing human GML tissue to normal mucosa [ 24 ] and chronic gastritis [ 25 ]. Both miR-142 and miR-155 inhibit the pro-apoptoticstress-induced P53 target gene (TP53INP1), thus accelerating MALT lymphoma proliferation [ 23 ]. Fernandez et al proposed the use of the quantitative expression of miR-142-3p and miR-155 to better distinguish between chronic gastritis and gastric MALT lymphoma.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…pylori -induced gastric lymphomagenesis in a mouse model and compared the miRNA expression profile obtained in the GML mouse model to that in human. They revealed the upregulation of a series of chemokine ligand, interleukin, tumor necrosis factor, miR-150, miR-155, miR-196a and miR-138 could be involved in the pathogenesis of GML [ 40 , 41 ]. Consistent with this, in this study, by transcriptomic analysis, we found some miRNA and chemokine ligand may take roles in the pathogenesis of GML.…”
Section: Discussionmentioning
confidence: 99%